Economic Impacts of Industry 4.0 - Dereli, Deniz Dilara; Sağlar, Uğur (IJOPEC Publication Limited, 2018)
Industrialization leads to drastic changes in all areas of life. The world is on the verge of the fourth industrial revolution by the effect of transformations in production technologies, which today, is called Industrial 4.0. The process indicates significant transformations in countries’ production structures, through which cyber systems are integrated with physical systems and the tools of production communicate with each other via internet. While digitizing production processes give speed, flexibility and efficiency to production, the growth rates and competitiveness of the countries increase. The change in the production structures of the countries leads to increases in the production capacities, while the economic life is reshaped in terms of growth, productivity, investment and employment. In this context, this paper explains the main characteristics and principles of Industry 4.0 and discusses the possible impacts of Industry 4.0 on economy.
Keywords: Industry 4.0; Production; Growth